(untitled) (Czech Journal of International Relations, 1994)
Schiller’s quote is often used to show that less than two centuries ago, "Germany" as a political entity did not yet exist. The only two elements that then held "Germany" and Central Europe together were culture (rather than a political entity called the state) and an "idea of ​​empire" based on the legacy of the Roman Empire combined with the medieval idea of ​​universal Christianity. This idea was radically revised during the 19th and 20th centuries with the advent of ethnic nationalism. Furthermore, it was not possible to erect a modern political structure over the old empire, and until now the generally widespread opinion prevailed that "Germany" represents a geographical entity in the center of Europe, whose western border was very well defined already in Roman times, in contrast to the eastern border, which remained in during the last two centuries in a state of constant uncertainty. In order to understand what Central Europe is, before we define its relations with East and West, we must define the position of "our own Germany" in the center of Europe, especially with regard to the special phenomenon called Mitteleuropa. Many confusions cause the difficulty to correctly interpret these two phenomena in the correct temporal and spatial relationship. Furthermore, the frequent stereotype that the term Mitteleuropa appeared only after the publication of the bestseller of the same name by Friedrich Naumann in 1915 must be corrected.’ In fact, attempts to define Mitteleuropa predated Naumann’s book by a good hundred years and appeared around the same time as the concept of Greater Germany. Since the French Revolution, these two concepts - Mitteleuropa and GroBdeutschland - have become inseparable like a pair of conjoined twins. Being aware of this amazing connection is important today, when we have to deal with a united Germany searching for a new identity. And when political ideas are created and "produced" in a specific spatial environment (erdgebunden), as the German geographer Ratzel would say.